Behavior of Concrete Slabs Reinforced by Different Geosynthetic Materials. Issue 1 (31st December 2022) - El-Hanafy, Ahmed M.; Alharthy, Samiha E.; Anwar, Ahmed M.
ABSTRACT: This research aims to examine experimentally the behavior of concrete slabs reinforced by different geosynthetic materials, which would help in assessing the utilization of geogrids and fibers for concrete structures. Therefore, three different geogrid sorts and polypropylene fibers were used in reinforcing concrete slabs. Six concrete slab specimens having dimensions of 1000 × 1000 x 100 mm (Plain, steel, fiber and geogrid reinforced concrete slabs) were fabricated and tested under a static bending load. The stress-strain, mid span deflection, crack pattern, and failure mechanism of the slabs were recorded during loading. Experimental results of this study prove that reinforcement using geosynthetic improved the load-carrying capacity, displacement, flexural strength, and delayed the collapse failure of concrete slabs except Geocell reinforcement as it reduces failure load compared to plain concrete slab due to debonding failure.